PEOPLE, PROCESS, AND ENVIRONMENT AS DRIVERS OF SUSTAINABLE PROJECT EFFECTIVENESS: AN SEM STUDY IN THE STEEL INDUSTRY - Dey, Biplab Kumar; Sarkar, Souren (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Industries are under increasing pressure to deliver economic performance while also minimizing their impact on the environment and society. There are only a few studies that investigate the link between human factors, process capabilities, business environments and sustainability practices in heavy industries. The current study fills those gaps with an integrated solution with a three-organizational-drivers framework. Factors related to people, processes and business environment are analysed as predictors of sustainability practices and sustainable project effectiveness in the steel industry. For the purpose of testing the relationship between people factors, process capability, business environment conditions, sustainability practices and sustainable project effectiveness in Steel Projects, quantitative cross sectional design was used in the study. Responses have been gathered from 350 professionals from steel companies throughout India. People factors improved sustainability practices and sustainable project effectiveness. Process capability improved sustainability practices and sustainable project effectiveness. Business environment conditions improved sustainability practices and sustainable project effectiveness. Sustainability practices improved sustainable project effectiveness. People factors showed the strongest total effect on sustainable project effectiveness. The results indicate that a good organizational system fosters good sustainability practices which in turn help produce good sustainable project effectiveness in steel projects.